Disinformation and Democratic Resilience in the European Union: Lessons from the Covid 19 Pandemic and Election Interference - Marsili, M. (Studia Administracji i Bezpieczeństwa [Public Administration and Security Studies], 2025)
This article investigates how the European Union has addressed the challenges posed by disinformation in times of crisis. It examines the EU’s institutional and regulatory responses to digital threats, with a particular focus on the COVID-19 infodemic and foreign election interference. The article analyzes key policy initiatives, including the Code of Practice on Disinformation, the Digital Services Act, and the establishment of the European Digital Media Observatory. Drawing on the social amplification of risk framework and resilience theory, it evaluates the effectiveness of these measures in fostering democratic stability and media integrity. The findings highlight both achievements and ongoing vulnerabilities in the EU’s strategy for countering information manipulation in a fragmented digital environment.